The Use of Whatsapp by the Cimahi Police Bhabinkamtibmas Unit in Preventing Motor Vehicle Theft Cases - Fitriani Akrima (Advances in Police Science Research Journal, 2021)
The background to this problem arises because of the curanmor case by the community in Cimahi City. An approach was made with the community through counseling by conveying messages of prevention of curanmor using the WhatsApp application carried out by bhabinkamtibmas. The research aims to determine whether the use of WhatsApp as a communication medium by the bhabinkamtibmas has been effective in carrying out their duties, as well as the factors affecting the use of WhatsApp which require a system or mechanism to simplify the duties of the bhabinkamtibmas. Concepts and theories for analyzing research focus. The research concept includes communication media, WhatsApp is used to prevent curanmor, bhabinkamtibmas in conveying messages, the concept of prevention, the concept of curanmor, Perkap Number 21 of 2007, Perkap Number 3 of 2015. Theory includes U&G Theory (Uses and Gratifications) and Management Theory. The systematic research method is a qualitative approach. This type of research is descriptive analytic. Primary and secondary data sources. Data collection techniques with interviews, observation, and document review. The location is in the Cimahi Police Binmas Unit. Validity by triangulation. Data analysis using interactive model analysis. The results of the study found that the use of WhatsApp analyzed by articles 8 and 9 of Perkap Number 21 of 2007 and Perkap Number 3 of 2015 was optimal. Influencing factors are internal factors that are analyzed with management elements and external factors consisting of the social conditions of the Cimahi city vulnerability, supporting factors from other functions, cooperation with other agencies and the implementation of bhabinkamtibmas duties in accordance with the SOP. Conclusion on the implementation of the effectiveness of WhatsApp as a communication medium by the Community Service Center to prevent curanmor cases can be carried out optimally. Constructive suggestions include suggestions for optimizing the implementation of the use of WhatsApp to convey messages of prevention of corruption to the public as well as optimizing internal and external factors that affect the task of community service through the WhatsApp application.